Short Communication: Species diversity, habitat and abundance of Culicid mosquitoes in Bushehr Province, South of Iran - MAHDI KHOOBDEL; DVOUD KESHAVARZI; HOSSEIN SOBATI; MORTEZA AKBARI (Society for Indonesian Biodiversity, 2020)
Abstract. Khoobdel M, Keshavarzi D, Sobat H, Akbari M. 2020. Short Communication: Species diversity, habitat and abundance of Culicid mosquitoes in Bushehr Province, South of Iran. Biodiversitas 21: 1401-1406. Culicid-borne diseases are causes of substantial illness worldwide. Effective culicid control depends on up-to-date knowledge of ecology and dispersal of species. Hence, this entomological study was conducted from January - December 2017 to provide baseline data on the distribution and ecology of mosquitoes in the Southwest of Iran. In total, 2530 specimens belonging to 14 different species were collected and identified, as follows: Culex hortensis, Cx. laticinctus, Cx. mimeticus, Cx. perexiguus, Cx. pipiens, Cx. modestus, Cx. sinaiticus, Cx. theileri, Cx. torrentium, Cx. tritaeniorhynchus, Anopheles stephensi, An. superpictus, An.dthali, and An.subpictus. Diversity analysis indicated higher species richness for uninhabited areas (Margalef 1/86). The average of Shannon diversity index ranged from 1.98 to 2.10. Differences between urban and uninhabited areas were significant according to the diversity t-test (P = 0.024, t = 2.26). The analysis of beta biodiversity showed that rural and uninhabited areas were the closest environments in their specific composition (Whittaker index = 0.130). These findings could be useful in vector control program.